Perdarahan Uterus Abnormal et causa Suspek Myoma Geburt+Anemia Sedang: Studi Kasus - Shariff, Fonda Octarianingsih; Ningrum, Dewi (Medula, 2025)
The patient experienced complaints of bleeding from the genitals since 3 days ago and repeated since one month ago. At first the blood was just reddish spots, over time there was more and more, and the blood that came out was fresh, clotted blood accompanied by lower abdominal pain that spread to the waist. During bleeding, the patient uses approximately 10 40 cm pads a day. On physical examination, general condition/consciousness was found, both compos mentis and vital signs, general status examination revealed anemic conjunctiva (+/+), pale lips, and tenderness in the lower abdomen. Meanwhile, on external obstetric and gynecological examination, tenderness was found in the hypogastric region and bleeding appeared on internal examination. The working diagnosis in this case is Abnormal Uterine Bleeding et causa Suspected Myoma Gobert + Anemia based on clinical considerations, physical examination findings, and supporting examinations. On external obstetric and gynecological examination, tenderness was found in the hypogastric region and bleeding appeared on internal examination. In supporting examination, namely histopathological examination, the results showed Adenomyoma (Polyp of Cervix Uteri). Management in this case is curettage and extirpation